RETRACTED: POLITICAL DISCOURSE : A CRITICAL DISCOURSE ANALYSIS OF THE RESISTANCE OF ISLAMOPHOBIC IDEOLOGY IN IMRAN KHAN CONFERENCE TO UNGA - Arshad, Khushnood; Ahmad, Sulaiman; Sanah Waheed (JEE (Journal of English Education), 2021)
This article has been retracted because it was published in another journal. This article can be found at GLOBAL JOURNAL OF ADVANCED RESEARCH Vol. 7 No 6, December, 2020. http://gjar.org/publishpaper/vol7issue6/d1031r90.pdf